2011
DOI: 10.7498/aps.60.109701
|View full text |Cite
|
Sign up to set email alerts
|

Hawking radiation of dynamical Kinnersley black hole under the new tortoise coordinate transformation

Abstract: With two new tortoise coordinate transformations, Hawking effect from a dynamical Kinnersley black hole is investigated by using the improved Damour-Ruffini method. After the tortoise coordinate transformation, the Klein-Gordon equation can be written in the standard form at the event horizon. Then extending the outgoing wave from outside to inside of the horizon analytically, the surface gravity and the Hawking temperature can be obtained automatically. It is found that Hawking temperature of different points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In the past few decades, the thermodynamic properties of black holes have attracted increasing interest, and a considerable amount of work related to the thermal radiation of black holes has been done. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Starobinsky and Unruh have demonstrated that for a rotating black hole or a charged black hole, not only is there thermal radiation, but also nonthermal radiation. [18,19] In recent years, the study of the nonthermal radiation of black holes has also achieved a great deal of progress.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, the thermodynamic properties of black holes have attracted increasing interest, and a considerable amount of work related to the thermal radiation of black holes has been done. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Starobinsky and Unruh have demonstrated that for a rotating black hole or a charged black hole, not only is there thermal radiation, but also nonthermal radiation. [18,19] In recent years, the study of the nonthermal radiation of black holes has also achieved a great deal of progress.…”
Section: Introductionmentioning
confidence: 99%